(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to describe the representation of women’s existence in Fatima AlBanawi’s film Basma through the lens of Simone de Beauvoir’s existentialist feminism. The film portrays the struggles of Basma, a woman living under the patriarchal social structure of Saudi Arabia, which restricts her choices and personal freedom. Using a descriptive qualitative method and content analysis, this research identifies dialogues, scenes, and visual symbols that correspond to Beauvoir’s key concepts: The Other, immanence transcendence, and the existential project. The findings reveal that Basma is initially positioned as The Other through familial subordination, bodily surveillance, and social moral expectations. She then experiences immanence as her mobility and decisions are controlled by her father and society. However, through growing self-awareness and acts of resistance, such as demanding education, refusing domestic confinement, and leaving home, Basma enters a phase of transcendence. Ultimately, through writing and expressing her desire to build her own path, she initiates an existential project that affirms her freedom as a conscious subject. This study concludes that Basma not only critiques patriarchal norms but also illustrates a woman’s existential awakening aligned with Beauvoir’s theoretical framework. These findings enrich contemporary Arab film studies and contribute theoretically to understanding how women construct their existence within restrictive cultural spaces.